Insulin-Like Growth Factor Binding Protein 6 in Rheumatoid Arthritis: A Possible Novel Chemotactic Factor? - Alunno, Alessia; Bistoni, Onelia; Manetti, Mirko; Cafaro, Giacomo; Valentini, Valentina; Bartoloni, Elena; Gerli, Roberto; Liso, Arcangelo (Frontiers in Immunology, 2017)
Objectives: Immune cell migration from the bloodstream to target tissues is a hallmark of rheumatoid arthritis (RA) pathogenesis. The role of chemoattractants, mainly chemokines, and their possible targeting for therapeutic purposes have been under intense investigation over the last years but the results were not as satisfactory as expected. The insulin-like growth factor binding protein 6 (IGFBP6), a direct inhibitor of IGF-II, also exerts IGF-independent effects including tumor cell migration in vitro. We aimed to assess the expression of this protein in serum, synovial fluid and synovial tissue of RA patients and to identify its possible chemotactic role in this disorder. Methods: IGFBP6 was measured in RA patients and healthy donors (HD) sera by LuminexxMAP® technology and in synovial tissue of RA patients and osteoarthritis controls by immunofluorescence. The identification of circulating IGFBP6+ cells was evaluated by flow cytometry and an in vitro migration assay was arranged. Results: We demonstrated that IGFBP6 is able to induce greater in vitro migration of RA as compared to HD and OA T lymphocytes and is overexpressed in serum and synovial tissue of RA patients. This in vitro chemotactic activity can be partially inhibited by dexamethasone. Conclusions: Our findings suggest a pathogenic role of IGFBP6 in RA and support its possible targeting for therapeutic purposes.